The role of Asta Brata leadership in improving business sustainability in village credit institutions in Bali - Maharani, Ida Ayu Dinda Priyanka; Wiagustini, Ni Luh Putu; Baskara, I Gde Kajeng; Rahyuda, Henny (Edelweiss Applied Science and Technology, 2025)
This study aims to determine the effect of Asta Brata leadership and risk management on business sustainability, as well as the effect of Asta Brata leadership on business sustainability mediated by risk management. This study was conducted at 100 units of LPDs in Bali Province. There were 24 statement items in the questionnaire to measure Asta Brata leadership, business sustainability, and risk management. Model and hypothesis testing were carried out using PLS-SEM. The study results indicate a significant positive relationship between Asta Brata leadership and business sustainability. Risk management has a positive and significant relationship with business sustainability. The results of the mediation test indicate that risk management consistently plays a role in mediating the effect of Asta Brata's leadership on business sustainability. Theoretically, this study contributes to the theoretical framework by introducing risk management as a mediating variable. In addition, this study contributes theoretically by proving that RBV is needed to improve business sustainability. This study provides a practical contribution for LPD leaders, namely implementing the principles of leadership based on Balinese local wisdom, Asta Brata, to improve sustainability.